Routine Activity Theory, Tax Knowledge, and Tax Compliance: An Empirical Evidence from Malaysian High-Income University Staff - Sritharan, Nivakan; Salleh , Nurul Ilma; Chang, Jacqueline Siak Gek (International Business Education Journal, 2025)
This study examines the relationship between tax knowledge and tax compliance among Malaysian high-income earning university staff, using Routine Activity Theory as the theoretical framework. The study utilized a sample size of 500 high-income university staff members and employed Pearson correlation for statistical analysis. Out of the 419 received responses, 172 valid responses were used from the high-income group. The survey collected demographic information, tax knowledge, and tax compliance data using dummy variables and Likert scales. The findings demonstrate a significant negative correlation (-0.751, p < 0.05) between tax knowledge and tax compliance. This suggests that individuals with higher tax knowledge may exploit loopholes and engage in non-compliance. These findings challenge the conventional belief that increased tax knowledge promotes compliance. The study emphasizes the importance of integrating tax education with information on penalties for non-compliance to address this issue. The findings suggest significant implications for tax policy reform and educational programs aimed at improving tax compliance. Practical implications include the development of targeted tax education programs and stricter enforcement strategies. Additionally, the study highlights the relevance of Routine Activity Theory in understanding taxpayer behavior, as higher tax knowledge could potentially identify "suitable targets" for non-compliance. Future research should consider objective measures of tax compliance and explore potential serial mediation effects. This study contributes to the existing literature by providing insights into the complex dynamics between tax knowledge and compliance among high-income university staff in Malaysia.